Bridging the Green Gap: Millennials and Gen Z’s Willingness to Pay More for Eco-Friendly Products in Indonesia - A. Nurul Suci Amaliah; Kiki Resky Ramadani Sucipto; Siti Aisyah; Aulia Rahmawati (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
Sustainable consumption is a substantial obstacle in contemporary society, particularly for millennials and Generation Z. Their sensitivity to pricing distinguishes these demographics, their willingness to make discerning product choices, and their preference for environmentally and socially responsible commodities. It is essential to comprehend their behaviours to formulate strategies that encourage sustainable consumption. This study utilises green signal factors to examine consumers’ willingness to pay more. A quantitative research method was employed, surveying 800 Millennials and Gen Z in Indonesia. This research utilises a Structural Equation Model-Partial Least Squares (SEM-PLS) methodology, employing SmartPLS software for data analysis. The results show green future estimation and perceived quality as strong predictors of a willingness to pay for more eco-friendly products. Although environmental concern does not significantly impact this willingness, the relationship remains positive. In contrast, green perceived benefits do not have a significant effect. These results emphasise that, despite a clear preference for sustainable products, consumers’ hesitation to pay additional costs reflects the complex interplay between economic considerations and environmental values.